An Integrated Management Model of World Class Education: The Synergy of Strategic Leadership, Operational Standardization, Marketing-Entrepreneurship, and International Cooperation at President University - Muzaki, Muzaki; Latif, Mukhta; Syhran, M.; Kholid, Idham; Murison, Murison (Lembaga Teewan Journal Solutions, 2026)
This research aims to build an integrative model of World Class Education (WCE) management at President University by synthesizing strategic leadership, operational standardization, marketing-entrepreneurship, and international cooperation. Using a qualitative, integrative document-based case study design, data were drawn from three 2026 mini-research manuscripts addressing leadership and operational standards, marketing-entrepreneurship in education, and higher education internationalization, enriched with institutional documents, official websites, and relevant literature. Analysis involved source mapping, thematic coding, pattern matching, cross-script synthesis, and conceptual proposition development. Findings show WCE is ineffective when managed as separate programs: strategic leadership guides vision, operational standardization ensures quality consistency, marketing-entrepreneurship links market understanding with value creation, and international cooperation expands learning, research, cultural, and industry networks. The case's strengths lie in its international positioning, English-language instruction, portfolio-building curriculum, the Jababeka industrial ecosystem, entrepreneurial incubation, academic mobility, and multicultural experience. Key gaps remain in cross-unit data integration, active partnership verification, measurement of startup and alumni outcomes, and collaborative research strengthening. The study's novelty is the 4I-WCE Integrative Model—strategic initiation, operational institutionalization, value innovation, and impactful internationalization, positioning WCE as an integration platform for institutional quality and evidence-based graduate competitiveness.